Development of a damage tolerant structure for nano-composite radar absorbing structures. (January 2015) - Lee, Dongyoung; Choi, Ilbeom; Lee, Dai Gil
Abstract: A radome structure, which is the protective cover for a radar antenna, is generally made of composite materials that have the high mechanical properties and low dielectric constants that are required for radome structures. Radar absorbing structures (RAS) are made of materials similar to radome structures, but include electro-conductive materials to enhance electromagnetic (EM) wave absorption characteristics. Though composite structures have both excellent electromagnetic and mechanical properties, they are vulnerable to external impact loads. When the RAS is damaged by external impact loads during operation, damages such as cracks, delamination, and dents may be generated, which can change the EM wave reflection properties of the composite structure. In this study, the surface of a RAS containing conductive nano-material was padded with ultra-high molecular weight polyethylene fabric to protect the composite structures against external impact loads. The impact characteristics of the RAS were investigated by drop weight impact tests with and without the pad, whose effect was measured by a compression test after impact (CAI). Additionally, the EM wave reflection characteristics of the padded RAS were investigated with a free space measurement. Finally, an optimum combination of UHMWPE fabric and glass composite face was suggested for the damage tolerant RAS structure.